Analyzing citation patterns of New Investigators Special Interest Group members - Kwon, Jae-Yung; Kaur, Manraj; Van Der Weijst, Lotte; Ahmed Osman, Ahmed Mohamed Yehia Naguib; Elsman, Ellen; Mehdipour, Ava; Lo, Lori Suet Hang (Springer Nature, 2024)
Aims: New investigators, including graduate students, recent doctoral graduates and early-career faculty (within 5 years of their terminal degree) play a pivotal role in advancing Quality of Life QoL) within the International Society of Quality of Life Research (ISOQOL). In this study, we analyzed the citation patterns of research outputs from ISOQOL New Investigators Special Interest Group (NI SIG) members to identify research trajectories and emerging areas of interest, fostering collaboration among the next generation of QoL researchers. Methods: We focused on NI SIG members, excluding 16 who did not meet the eligibility criteria. Among the remaining 61 members, we examined published documents (including peer-reviewed articles, books, editorials, and meeting abstracts) authored or co-authored by NI SIG members. Our search spanned the Web of Science databases from 2019 to 2023. We conducted bibliometric descriptive analysis to explore publication trends and citations. Additionally, we performed thematic analysis of extracted documents using the Bibliometrix package in R. Results: Our analysis encompassed 784 documents, revealing an average of 11 co-authors and 34.7% international collaborations per document. Document publication peaked in 2022 (211) but declined in 2023 (183), with a corresponding drop in average citations per article from 5.24 to 1.03. Most documents were published in the Quality of Life Research (144), BMJ Open (23), and Journal of Patient-Reported Outcomes (14) with many clinical-focused journals being cited only once (243). Thematic mapping highlighted established themes such as QoL research or instrument validation, health or impact of intervention, and the use of the European Organization for Research and Treatment of Cancer (EORTC) questionnaire. Emerging research areas included job satisfaction, health workers, and research guidelines (see Fig. 1). The corresponding authors of published documents were primarily from high-income countries including the United States, Canada and the United Kingdom. Conclusion: This study underscores the robust international collaborations among NI SIG members, yet highlights avenues for increased engagement, particularly among low and middle-income countries. It also elucidates the entrenched themes such as evaluating the impact of health and instrument validation in QoL research while unveiling niche or emerging areas for further exploration and collaboration.